2017
DOI: 10.4238/gmr16039788
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of Saccharum complex using ISSR markers

Abstract: Sugarcane (Saccharum sp, Poaceae) is native to Southeast Asia, and due to growing demand as raw material, its cultivation recently expanded to new frontiers. The genetic diversity analysis is essential for targeting strategies in the formation and maintenance of a germplasm. This study aimed to assess the genetic diversity of 26 accessions of sugarcane from the Active Germplasm Bank of Embrapa Coastal Tablelands, using inter-simple sequence repeat (ISSR) molecular markers. Sixteen primers were used, resulting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 19 publications
1
8
0
1
Order By: Relevance
“…To determine the ideal number of amplified fragments necessary to study genetic diversity in natural populations, the correlation value (r) of the similarity and stress matrix values (E) was estimated. According to Oliveira et al (2017), these values indicate the fit between the original matrix and the simulated matrix. The optimal number of fragments was calculated by the GENES software (Cruz, 2007), being considered satisfactory when the stress value was less than 0.05 (Kruskal, 1964) and the correlation was close to 1.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the ideal number of amplified fragments necessary to study genetic diversity in natural populations, the correlation value (r) of the similarity and stress matrix values (E) was estimated. According to Oliveira et al (2017), these values indicate the fit between the original matrix and the simulated matrix. The optimal number of fragments was calculated by the GENES software (Cruz, 2007), being considered satisfactory when the stress value was less than 0.05 (Kruskal, 1964) and the correlation was close to 1.…”
Section: Discussionmentioning
confidence: 99%
“…Originária das regiões tropicais do sul e sudeste da Ásia, a cana-de-açúcar (Saccharum spp), pertencente à família das Poaceae (OLIVEIRA et al, 2017), tem expressiva utilização na produção de açúcar e etanol em razão da elevada concentração de açúcares e à grande demanda do mercado mundial por estes produtos .…”
Section: Introductionunclassified
“…Among them, the ISSR are widely used because they do not require previous information of the DNA sequence (universal primers); have a low development cost; present high interspecific transferability; and; most importantly, produce a high level of polymorphic information (Barth et al, 2002;Brandão, 2011). A number studies with ISSR have demonstrated their efficiency (Costa et al, 2018;Oliveira et al, 2017;Chagas et al, 2015;Dias et al, 2015;Rossi et al, 2014;Moulin et al, 2013;Rossi et al, 2009;Brandão, 2011;Cidade et al, 2008;Almeida et al, 2012).…”
Section: Introductionmentioning
confidence: 99%